Becoming an emotionally intelligent teacher - Powell, William R.; Kusuma-Powell, Ochan; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2010)
William Powell and Ochan Powell's book guides teachers through the process of developing and enhancing their emotional intelligence in order to reap benefits in the classroom. The text provides teachers with the essential research, case studies, and practical tools for strengthening their emotional intelligence skill set.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Affective education; Emotional intelligence; Emotions and cognition; Electronic books